Assisted Fertilization in Peru. - Beuermann Cancino, Christian (2015)
Our work consisted in the study included ten infertile couples between July 1989 and May 1990, of which the average age of the patients was 34.6 years (2742) with a duration of 6.4 years Sterility (3-15 ). The cause of sterility in 100% of 108 cases was bilateral tubal obstruction, eight of which as a result of severe adherence syndrome as a result of previous surgery, either gynecological or general surgery interventions (Appendectomies, peritonitis, etc.), in one case associated with mild endometriosis and the latter is the result of genital tuberculosis.